Pyometra with Babesiosis in a Bitch - A Case Report - Renu; Boyal, Pramod Kumar; Mehra, Manisha; Meena, Abhay Kumar; Kumari, Shubita (International Journal of Bio-resource and Stress Management, 2025)
The present study investigated a case report of pyometra with canine babesiosis in a dog during March, 2025 at VCC, PGIVER, Jaipur, India. A two year-old unspayed female dog German shepherd weighing 28 kgs with the history of decline in body weight, anorexia, dehydration, swollen vulva, uterine pus discharge with foul smell, vomiting. polydipsia, polyuria, lethargy, weak pulse with shallow respiration and elevated temperature (104°F) presented to Department of Veterinary Clinical Complex. Clinical examination revealed pinkish mucus membrane and slightly distended abdomen with pain on palpation. Hematology revealed normal hemoglobin level, normal PCV value, normal total erythrocyte counts, slightly elevated total leucocyte count, neutrophilia, lymphocytopenia, and eosinophilia. Thrombocytopenia was also observed in this case. Mean corpuscular volume (MCV) and Mean corpuscular hemoglobin (MCH) were normal. Mean corpuscular hemoglobin concentration (MCHC) was slightly increased. Left shift of neutrophills was also seen in blood smear. Blood biochemical test revealed normal values of Alanine Aminotransferase (ALT), Alkaline Phosphatase (ALKP), Creatinine, Blood urea nitrogen, and Creatinine BUN ratio. Diagnosis was made by history, clinical symptoms and ultrasonography. Ultrasonography revealed an enlarged uterus with thickened wall and pus filled tubular horns. There were multiple, round, oval fluid filled pouches was also seen along the uterine horn. These pouches of pus were separated by thin septa. The microscopic examination of the thin blood smear revealed the presence of Babesia organisms.